Polypharmacy in a hospitalized psychiatric population: risk estimation and damage quantification - J. Carmona-Huerta; S. Castiello-de Obeso; J. Ramírez-Palomino; R. Duran-Gutiérrez; D. Cardona-Muller; F. Grover-Paez; P. Fernández-Dorantes; R. Medina-Dávalos (BMC Psychiatry, 2019)
Abstract Background Polypharmacy increases the risk of pharmacological interactions, prevalence of secondary effects and with this the lack of adherence to treatment. It is estimated that between 10 and 40% of patients hospitalized in psychiatric institutions are prescribed more than one antipsychotic. The objective of the present study was to identify the prevalence of polypharmacy, evaluate adverse effects associated to the use of psych drugs and to estimate the risk in specific groups. Methods We carried out a longitudinal, retrospective study that included the analysis of all discharged patients (n = 140) in the first trimester of the year in a psychiatric hospital in Mexico. The information was classified into 7 sections: sociodemographic, diagnosis, clinical follow-up information, prescribed drugs, adverse reactions, substance abuse, laboratory and complementary results. Risk estimation was obtained with Odds Ratios, to correlate continuous variables Pearson’s correlation was used. Student’s T and Mann Whitney’s U were used to compare 2 independent samples; multiple and linear regressions were carried out. Results The mean number of drugs used during hospitalization was 7.8 drugs per patient. The mean prescribed psych drugs was 4.07. The mean antipsychotic dose was the risperidone equivalent of 5.08 mg. 29.2% of patients had at least one secondary effect associated to the use of drugs, 17.8% presented extrapyramidal symptoms. 81.4% of patients were prescribed 6 or more drugs (polypharmacy) and were 5 times more likely to suffer a secondary effects (OR 6.24). 14.2% had polypharmacy while receiving antipsychotics and had more than twice the risk of presenting extrapyramidal symptoms (OR 3.05). For each added psych drug, hospital stay increased by 6.56 days. Conclusions Despite international guideline recommendations where reasoned and conciliatory prescription of psych drugs is advised, there is still a high prevalence of polypharmacy in patients hospitalized in psychiatric institutions. In the present study 4 out of 5 patients received polypharmacy decreasing tolerability, treatment adherence and increasing the risk and costs secondary to an increased hospital stay.